Utilization Of Carbon Nanotubes In Electromagnetic Wave Detectors - Muhammad Hanis Zakariah; Poppy Puspitasari (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
Direct detection of hydrocarbon by an active source using electromagnetic (EM) energy termed seabed logging (SBL) has shown very promising results. However, currently available electromagnetic wave technology has a number of challenges include sensitivity and frequency matching. This paper presents development of the carbon nanotubes (CNTs) as electromagnetic wave detector due to outstanding properties of carbon nanotubes. They are currently one of the desired materials for advanced technologies. Two types of detectors were developed in this work, carbon nanotube-based (D1) and without nanotube-based (D2) detectors. Various configuration and arrangement for each type of detector were investigated to determine the one with the highest detection measurement and stability of frequency stability of detection system. It was found that 20 turn-coils coil placed at its centre gives the maximum detection of induction voltage, 39.61 mV. However, the 20 turn- coils with CNTs which gives 36.50 mV is the preferred EM detectors due to the stability in frequency of the detection system.